The reality of the use of management control tools in ‎economic institutions: ‎‏- ‏Maintenance Directorate of ‎Sonatrach Institution in Laghouat as a model‏ -‏ - Bouhali, Kheira; Khelil, Abderrazak (Dirassat Journal Economic Issue, 2017)
The main concern of thisstudyis to spot light on the use of management controlTools in the maintenance department in Laghouat. The most important tools are the analyticalaccounting, budgets and dashboard. Thesetoolsplaysignificantroles in planning, coordination, control and decisionmaking. In thisstudy, however, a hugeemphasiswillbegiven to the last tworoles. Wefoundthatthis direction relies on thesetools in the control via analyzing the divergences eachmonth, and accordinglydecisions are takenbased on the given information to avoidanyrecurrence.